2008
DOI: 10.1248/bpb.31.1794
|View full text |Cite
|
Sign up to set email alerts
|

Anti-methicillin Resistant Staphylococcus aureus (MRSA) Compounds Isolated from Laurus nobilis

Abstract: We found that an extract from Laurus nobilis L. (Lauraceae) leaves showed antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). We purified two flavonoids as the effective compounds and identified them as kaempferol 3-O-a a-L-(2؆,4؆-di-E-p-coumaroyl)-rhamnoside (C2) and kaempferol 3-O-a a-L-(2؆-Zp-coumaroyl-4؆-E-p-coumaroyl)-rhamnoside (C3). Both compounds showed strong antibacterial activity not only against MRSA but also against vancomycin-resistant enterococci (VRE). There was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 24 publications
3
52
1
3
Order By: Relevance
“…Teffo et al (2010) reported that kaempferol and its glycosides are well known for their pharmacological activities including antibacterial activity. It is worth to note, the presence of 4' hydroxyl substitution in the B ring, 5,7-dihydroxyl substitutions in the A ring and the substitution with 3-O-acyl chains in the C ring enhanced the anti-staphylococcal activity of flavonoids and that support the earlier findings of Otsuka et al (2008).…”
Section: Discussionsupporting
confidence: 85%
“…Teffo et al (2010) reported that kaempferol and its glycosides are well known for their pharmacological activities including antibacterial activity. It is worth to note, the presence of 4' hydroxyl substitution in the B ring, 5,7-dihydroxyl substitutions in the A ring and the substitution with 3-O-acyl chains in the C ring enhanced the anti-staphylococcal activity of flavonoids and that support the earlier findings of Otsuka et al (2008).…”
Section: Discussionsupporting
confidence: 85%
“…Staphylococci are frequently refractory to many new and commonly used antimicrobial agents and have become a problem in recent years (8,12,17). Methicillin (meticillin)-resistant Staphylococcus aureus (MRSA) infections have emerged as a worldwide problem, and clinical strains of MRSA exhibit reduced susceptibility to antimicrobial agents (18).…”
mentioning
confidence: 99%
“…Potent antibacterial activities of licorice phenolics against bacterial strains such as Helicobacter pylori, cariogenic bacterial species, Streptococcus mutans and Streptococcus sobrinus, and periodontopathogenic species, Porphyromonas gingivalis and Prevotella intermedia, were also reported [5][6][7][8]. Our previous investigation revealed that several naturally occurring compounds showed potent antibacterial effects on methicillin-resistant Staphylococcus aureus (MRSA) [9][10][11], and some of the licorice phenolics, such as licoricidin (1), showed suppressing effects on the oxacillin resistance of MRSA [11].…”
Section: Introductionmentioning
confidence: 93%
“…Estimation of antibacterial effects of licorice phenolics on vancomycin-resistant Enterococcus strains was carried out as has been described in the literature [9,43,44]. Enterococcus faecium FN-1 and E. faecalis NCTC 12201 used in this study were vancomycin resistant ones which were kindly provided by Dr. Y. Ike, Gunma University.…”
Section: Antibacterial Assaymentioning
confidence: 99%